2013
DOI: 10.1111/mec.12549
|View full text |Cite
|
Sign up to set email alerts
|

Tracing horizontal Wolbachia movements among bees (Anthophila): a combined approach using multilocus sequence typing data and host phylogeny

Abstract: The endosymbiotic bacterium Wolbachia enhances its spread via vertical transmission by generating reproductive effects in its hosts, most notably cytoplasmic incompatibility (CI). Additionally, frequent interspecific horizontal transfer is evident from a lack of phylogenetic congruence between Wolbachia and its hosts. The mechanisms of this lateral transfer are largely unclear. To identify potential pathways of Wolbachia movements, we performed multilocus sequence typing of Wolbachia strains from bees (Anthoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 96 publications
2
74
1
2
Order By: Relevance
“…; Gerth et al . ) and rarely observed in real time in the field (Schuler et al . ), it does not necessarily lead to a successful establishment in new populations.…”
Section: Discussionmentioning
confidence: 99%
“…; Gerth et al . ) and rarely observed in real time in the field (Schuler et al . ), it does not necessarily lead to a successful establishment in new populations.…”
Section: Discussionmentioning
confidence: 99%
“…Kyei-Poku et al (2005) reported similarities among wsp isolates suggestive of horizontal transfer among species of lice (Anoplura, Mallophaga) that are neither predators nor have any known parasitoids. Gerth et al (2013) compared the diversity of Wolbachia infections associated with bees (Hymenoptera) that shared either a taxonomic affinity or an ecological association, and concluded that the latter was insufficient to explain observed patterns. Phylogenetic interpretations are confounded with use of wsp sequences, because the gene is prone to recombination (Baldo et al, 2005).…”
Section: Horizontal Transfer Of Wolbachia Infectionsmentioning
confidence: 98%
“…Similar difficulties have been reported by others. Examples include the failure to obtain complete sets of MLST sequences for Wolbachia isolates from a weevil (Coleoptera: Curculionidae), species of aphids (Hemiptera) (Augustinos et al, 2011) and from species of bees (Hymenoptera) (Gerth et al, 2013). As concluded by Augustinos et al (2011), further work is needed to improve detection and characterization of Wolbachia isolates across diverse host taxa.…”
Section: Genotyping Of Wolbachia Strains With Mlstmentioning
confidence: 98%
“…There is growing evidence for common horizontal transmission of Wolbachia from one species to another (Ahmed et al , 2013; Gerth et al , 2013; Brown and Lloyd, 2015), and the transmission route is becoming a hotspot of research, given its importance in ecological and evolutionary biology (Vavre et al , 1999; Sintupachee et al , 2006; Caspi-Fluger et al , 2012; Gehrer and Vorburger, 2012). Recently, Wolbachia horizontal transmission through invertebrate predators and parasitoids has been revealed (Huigens et al , 2000, 2004; Le Clec'h et al , 2013; Ahmed et al , 2015).…”
Section: Introductionmentioning
confidence: 99%